THE CONCEPT OF MASLAHAH IN ISLAMIC FINANCIAL LITERACY AMONG YOUTH IN BANK NEGARA MALAYSIA MUSEUM ART AND GALLERY - Mahphoth, Mohd Halim; Sulaiman, Zuraidah (Fakultas Syariah, 2020)
The effort to enhance financial literacy has become extremely important and is complementary to the initiative by Consumer Credit Act in order to strengthen the credit consumer protection framework in Malaysia. Therefore, Bank Negara Malaysia Museum Art and Gallery (BNM MAG) educates the public through exhibits that foster visitorsâ€™ understanding of financial knowledge especially the Sharia compliant matters at their Islamic Finance Gallery. This study examined the relationships between satisfying experiences and generic learning outcomes of youth visitors at BNM MAG. The study examined three key satisfying experiences that had significant and positive effects on the generic learning outcomes of youth visitors including affective, cognitive and sensory experiences. However, social experiences were not significant towards generic learning outcomes on youth visitors. This study provides insights and drive efforts to promote effective delivery of financial education initiatives to Malaysians in a sustainable manner. The authors expect that policymakers or museum managers could make use of the findings to improve Malaysiansâ€™ financial literacy in general, thus helping Malaysians making informed financial decisions. The study contributes to the advancement of Islamic financial education for the youth with the purpose of improving creative and productive attitudes.Upaya meningkatkan literasi keuangan menjadi sangat krusial dan mendukung inisiasi Undang-Undang Kredit Konsumen untuk memperkuat kerangka perlindunganÂ kredit konsumen di Malaysia. Maka, Bank Negara Malaysia Museum Art and Gallery (BNM MAG) mengedukasi masyarakat melalui pameran yang memberikan pemahaman kepada pengunjung tentang keuangan khususnya yang berhubungan dengan syariah di Islamic Finance Gallery (Galeri Keuangan Syariah). Studi ini mengkaji hubungan antara kepuasan pengalaman dan hasil pembelajaran umum (generic learning outcomes/GLO) yang dialami pengunjung muda di BNM-MAG. Ada acuan kepuasan pengalaman yang dijadikan objek studi yang memiliki efek signifikan dan positif terhadap GLO di kalangan pengunjung muda termasuk pengalaman afektif, kognitif, dan sensori. Meskipun begitu, pengalaman sosial para pengunjung tidak signifikan terhadap GLO. Studi ini memberi wawasan dan mengenalkan usaha untuk mengenalkan penyampaian yang efektif tentang inisiasi pendidikan keuangan pada warga Malaysia dengan cara yang berkelanjutan. Penulis berharap agar pembuat kebijakan atau pengolah museum dapat memanfaatkan temuan ini untuk meningkatkan literasi keuangan warga Malaysia secara umum, dengan demikian membantu mereka untuk membuat keputusan keuangan yang tepat. Penelitian ini memiliki kontribusi meningkatkan pendidikan keuangan Islam bagi para pemuda dengan tujuan menumbuhkan sikap kreatif dan produktif.